Juridical Study of Corruption Crime in Indonesia: A Comparative Study - Abdullah, Abdullah (Scholar Center, 2022)
Corruption is an act of deviation that is against the law and the principle of justice (al-`adalah). Corruption with all its negative impacts produces various distortions in the life of the nation and state. In Islamic law, Corruption (jarimah) Crime is prohibited in the Qur'an and al-hadith. Fingers of corruption fall into the category of ta'zir punishment where the type of punishment is determined by the government (ulil amri) through a court decision so that perpetrators of corruption can be sentenced to imprisonment, fines, cut-offs hands (had), or even death if the government so wishes. In the aspect of Indonesian criminal law, the eradication of corruption is regulated in Law No. 31 of 1999 jo. Law No. 20 of 2001. This provision can ensnare perpetrators of corruption in both the private and public sectors. To increase the effectiveness of law enforcement against corruption, the government established the institution of the Corruption Eradication Commission (KPK) and the Court of Corruption. In addition, to facilitate the process of proving corruption offenses, this provision applies a reverse burden of proof.